Conditions of Formation of α- and β-Modifications of Ge3N4 and Preparation of Germanium Oxynitride Dielectric Films - Wardosanidze, Zurab V.; Nakhutsrishvili, Irakli; Kokhreidze, Revaz (Journal of Coating Science and Technology, 2024)
The binary compound of germanium with nitrogen (Ge3N4) is used in various fields of science and technology. Among the experimentally discovered and theoretically predicted crystal modifications of Ge3N4 at ordinary pressures and temperatures, only the α- and β-phases of the nitride are stable. There are conflicting data in the literature on the conditions for the formation of these phases. The main methods for obtaining Ge3N4 are the nitridation of elemental germanium and its dioxide with ammonia. The present work studied the influence of the degree of humidity of ammonia on the possibility of the formation of pure α- and β-phases and their mixtures. It is shown that it is possible to obtain nitride with practically any ratio of these phases by varying degrees of humidity and the temperature of the process. During the process, the formation of germanium nitride is accompanied by its simultaneous evaporation. Oxidation with water vapors also produces volatile monoxide. Simultaneous evaporation of germanium nitride and oxide results in the deposition of a film of germanium oxynitride in the cold zone of the reactor. This film is a germanium oxynitride used in microelectronics as a dielectric layer in Metal-Insulator-Semiconductor systems.